2009
DOI: 10.1029/2008ja013966
|View full text |Cite
|
Sign up to set email alerts
|

Neutral wind control of the Jovian magnetosphere‐ionosphere current system

Abstract: [1] In order to clarify the role of neutral dynamics in the Jovian magnetosphere-ionosphere-thermosphere coupling system, we have developed a new numerical model that includes the effect of neutral dynamics on the coupling current. The model calculates axisymmetric thermospheric dynamics and ion composition by considering fundamental physical and chemical processes. The ionospheric Pedersen current is obtained from the thermospheric and ionospheric parameters. The model simultaneously solves the torque equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
115
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(126 citation statements)
references
References 47 publications
11
115
0
Order By: Relevance
“…Typical values for the auroral electron characteristics are highlighted in bold in Table 2 and yield Pedersen conductance values in the 1.5-2 mho range at Jupiter and in the 10-15 mho range at Saturn (see Table 2). These jovian values are supported by estimations from field-aligned potential models -using parameterized Pedersen conductance relations: they spread from 0.7 to 1.5 mho (Smith and Aylward 2009;Tao et al 2009;Ray et al 2010). Therefore, difference in auroral forcing reduces the difference in conductances between Jupiter and Saturn down to one order of magnitude.…”
Section: Ionospheric Electrical Conductancesmentioning
confidence: 79%
See 2 more Smart Citations
“…Typical values for the auroral electron characteristics are highlighted in bold in Table 2 and yield Pedersen conductance values in the 1.5-2 mho range at Jupiter and in the 10-15 mho range at Saturn (see Table 2). These jovian values are supported by estimations from field-aligned potential models -using parameterized Pedersen conductance relations: they spread from 0.7 to 1.5 mho (Smith and Aylward 2009;Tao et al 2009;Ray et al 2010). Therefore, difference in auroral forcing reduces the difference in conductances between Jupiter and Saturn down to one order of magnitude.…”
Section: Ionospheric Electrical Conductancesmentioning
confidence: 79%
“…showed that the parameter k increases when the incident electron energy increases, while it decreases when the equatorward auroral voltage is enhanced. Tao et al (2009) found regions where the slippage can yield a height-dependent kz parameter larger than 1: this corresponds to a region where the neutral wind velocity is larger than the ion drift velocity in the planetary rotation frame caused by Coriolis forces and viscosity. For regions where kz < 1, they derived values for k between 0.25 and 0.35 over the 63-73…”
Section: Ionospheric Electrical Conductancesmentioning
confidence: 99%
See 1 more Smart Citation
“…IR light is emitted from thermally excited ions and molecules when they transition between vibrational and rotational states, thus the emitted IR intensity reflects the atmospheric temperature. The enhancement of H þ 3 in the high-latitude atmosphere (e.g., Miller et al, 1997;Satoh and Connerney, 1999) is mainly produced by incident auroral electrons through ion chemistry (e.g., Tao et al, 2009). Because of this close relationship of H þ 3 production with the auroral electrons of our interest, we focus on H þ 3 IR lines in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This coupled system is investigated using numerical models, where the neutral atmosphere is represented by a general circulation model (GCM), which is coupled to either a simplified model representing the currents Journal of Geophysical Research: Space Physics 10.1029 in the magnetosphere-ionosphere (MI) system (Ray et al, 2015;Smith & Aylward, 2009;Tao et al, 2009Tao et al, , 2010Tao et al, , 2014Yates et al, 2012Yates et al, , 2014Yates et al, , 2018 or by imposing electric fields directly into the thermospheric GCM (Achilleos et al, 1998(Achilleos et al, , 2001Bougher et al, 2005;Majeed et al, 2005Majeed et al, , 2009Majeed et al, , 2016Millward et al, 2002Millward et al, , 2005. This coupled system is investigated using numerical models, where the neutral atmosphere is represented by a general circulation model (GCM), which is coupled to either a simplified model representing the currents Journal of Geophysical Research: Space Physics 10.1029 in the magnetosphere-ionosphere (MI) system (Ray et al, 2015;Smith & Aylward, 2009;Tao et al, 2009Tao et al, , 2010Tao et al, , 2014Yates et al, 2012Yates et al, , 2014Yates et al, , 2018 or by imposing electric fields directly into the thermospheric GCM (Achilleos et al, 1998(Achilleos et al, , 2001Bougher et al, 2005;Majeed et al, 2005Majeed et al, , 2009Majeed et al, , 2016Millward et al, 2002Millward et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%